CO2 release during soil rewetting shapes the seasonal carbon dynamics in South American temperate region - Vardag, Sanam Noreen; Metz, Eva-Marie; Artelt, Lukas; Basu, Sourish; Butz, André (Geophysical research letters, 2025)
Processes driving the terrestrial carbon fluxes in the South American Temperate (SAT) region are not well understood due to limited availability of in situ and flux tower measurements. This study leverages atmospheric CO2 measurements by the Greenhouse Gases Observing Satellite to additionally constrain net carbon fluxes in the SAT region. By identifying Dynamic Global Vegetation Models that closely align with observational data, we pinpoint the processes driving the seasonal land-atmosphere CO2 exchange. We reveal that the onset of rainfall triggers an early increase in heterotrophic respiration while autotrophic respiration and gross primary production are delayed leading to an increase in net ecosystem exchange in September to October. Our findings suggest that soil rewetting processes in semi-arid areas dominate seasonal carbon dynamics and need to be accurately represented in global carbon cycle models to improve the global carbon budget.